Time for micro-RNAs in steatotic liver disease: a case–control study - Stoica, Victor Constantin; Apostol, Dimitri; Diculescu, Mihai Mircea; Gârdan, Iuliana Petronela; Gârdan, Daniel Adrian; Mărunțelu, Ion; Constantinescu, Ileana (Frontiers in Endocrinology, 2024)
One of the challenges of modern-day living is to resist the temptation of overfeeding and sedentariness and maintain a healthy body and mind. On a favorable genetic and epigenetic background, a high-fat diet combined with lack of physical exercise constitutes the foundation for severe metabolic disturbances including steatotic liver disease. In our case–control study, we had the aim of establishing the role of selected micro-RNAs—miR-122, miR-192, miR-33a, and miR-33b—as superior biomarkers for the diagnosis and prognosis of steatotic liver in a 36-patient cohort compared to 12 healthy controls. Initial results confirmed the decline in miR-122 expression as fatty liver is progressing. However, combinations of ΔmiRs, such as ΔmiR33a_192, ΔmiR33a_122, and ΔmiR33b_122, correlate with ultrasound steatosis grade (R2 = 0.78) while others such as ΔmiR33b_122 provide a high specificity and sensitivity in fatty liver disease with an area under the curve (AUC) of 0.85. Compared to classical biomarkers, micro-RNAs can be used for both diagnostic and prognostic purposes as their diminished expression in severe cases of steatosis is associated with higher risk of emerging hepatocellular carcinoma. Manipulating micro-RNAs through agomirs or antagomirs can be the answer to the yet unsolved problem of efficient therapy in MAFLD.